SECURITY AND THE GUARDIA CIVIL - Díez Nicolás, Juan (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
Security has become the most important value in today's societies. Recent data from over a hundred countries around the world show that most of the world's population considers security more important than freedom, although there are important exceptions. When differentiating between three levels of security – personal, community and national – in general, most people perceive more security in the place where they live, less in their personal security, and even less in the security of their country. The Guardia Civil as one of the Security Forces in Spain, has usually received a rating of more than 6 points on a scale of 0 to 10 points, along with the Crown Prosecution Service, the National Police Service and the Armed Forces. This article describes how the Guardia Civil has been assessed over the past few decades by different sectors of Spanish society, and attempts to explain the main variables behind this assessment.
Keywords: Guardia Civil; security; international; indexes; surveys